(untitled) - Yule, George (Oxford, 2006)
A three-level English grammar practice series for the classroom or self-study with clear explanations and lots of extra practice. Each level has an interactive Practice-Boost CD-ROM.
Ngữ pháp trung cấp
Keywords: English language,English language,Tiếng Anh; Textbooks for foreign speakers,Grammar,Giáo trình dành cho người nước ngoài